Diastereoselective Gold(I)-Catalyzed [2+2+2] Cycloaddition of Oxo-1,5-enynes - Calleja, Pilar; Muratore, Michael E.; Jiménez, Tania; Echavarren, Antonio M. (Synthesis, 2016)
The intramolecular gold(I)-catalyzed [2+2+2] cycloaddition of oxo-1,5-enynes bearing protected homopropargylic alcohols provides access to oxatricyclic adducts with good to excellent diastereoselectivity.
Keywords: gold; enynes; cycloisomerization; cycloaddition; Prins reaction